A Study of Suffix -En Usage Comprehension in Words by EFL Students at Tadulako University - Ahmad, Nur Anisa Fitri; Marhum, Mochtar; Patmasari, Andi; Manurung, Konder (Journal of English Language and Education, 2026)
This study investigates the extent of EFL students’ understanding of the suffix -en in English word formation at Tadulako University. This research employs a descriptive quantitative design, with data collected through a multiple-choice test and a questionnaire focusing on recognition, word formation, and meaning of the suffix -en. The data are analyzed using descriptive statistics. The findings indicate that students experience low difficulty in recognizing the suffix -en, moderate difficulty in understanding its meaning, and high difficulty in word formation using the suffix -en. These results suggest that students’ difficulties lie mainly in productive and semantic aspects rather than in formal recognition, indicating the need for explicit instruction focusing on word formation practice and contextualized meaning analysis.